2014
DOI: 10.1371/journal.pone.0091285
|View full text |Cite
|
Sign up to set email alerts
|

Mind Wandering, Sleep Quality, Affect and Chronotype: An Exploratory Study

Abstract: Poor sleep quality impairs cognition, including executive functions and concentration, but there has been little direct research on the relationships between sleep quality and mind wandering or daydreaming. Evening chronotype is associated with poor sleep quality, more mind wandering and more daydreaming; negative affect is also a mutual correlate. This exploratory study investigated how mind wandering and daydreaming are related to different aspects of sleep quality, and whether sleep quality influences the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
59
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 80 publications
(187 reference statements)
9
59
0
Order By: Relevance
“…As such, future studies should address this overlap and differentiation between MW, ADHD and maladaptive daydreaming. In addition, it is important to include sleep quality in future studies, as sleepiness or fatigue may contribute to MW (Carciofo, Du, Song, & Zhang, ).…”
Section: Discussionmentioning
confidence: 99%
“…As such, future studies should address this overlap and differentiation between MW, ADHD and maladaptive daydreaming. In addition, it is important to include sleep quality in future studies, as sleepiness or fatigue may contribute to MW (Carciofo, Du, Song, & Zhang, ).…”
Section: Discussionmentioning
confidence: 99%
“…Behavioral performance and scale scores analysis revealed that patients with ID who had poorer subjective sleep quality measured by PSQI showed worse subjective thought control ability and more negative affect. Previous studies have demonstrated that the higher frequencies of mind wandering, daydream, and negative thought intrusion were associated with poorer sleep quality, in particular with poorer subjective sleep quality (Baker, Baldwin, & Garner, 2015;Carciofo, Du, Song, & Zhang, 2014). Worrisome thought is a center feature of several models of insomnia and involves persistent intrusive thoughts, which may impair the cognitive control in insomnia patients (Borkovec, Robinson, Pruzinsky, & DePree, 1983;Harvey, 2002;Lundh & Broman, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, as noted earlier, across numerous studies, unguided thought has frequently been implied in researchers' conceptualizations of mind wandering (e.g., Blanchard et al, 2014;Carciofo et al, 2014;Christoff et al, 2016;Qu et al, 2015;Irving, 2016;Rummel & Boywitt, 2014; for more examples, see Seli, Risko, & Smilek, 2016a, Supplemental Materials), and such a conceptualization appears to be a sensible one.…”
Section: Thoughts That Are Unguidedmentioning
confidence: 83%
“…Indeed, intentionally occurring thoughts might seem to best reflect states wherein people actively guide their attention toward a task, which appear to be antithetical to our general conceptualization of mind wandering. It is presumably the case that, for this reason, some researchers have explicitly defined mind wandering in terms of unintentional thought (e.g., Blanchard et al, 2014;Carciofo et al, 2014;Qu et al, 2015;Rummel & Boywitt, 2014; for more examples, see Seli, Risko, & Smilek, 2016a, Supplemental Materials). One problem, however, with such a strict definition of mind wandering is that it excludes as cases of mind wandering situations in which people are at ease, sitting dreamily, allowing their thoughts to wander, or cases in which an individual deliberately neglects the task at hand in the service of entertaining TUT.…”
Section: The Intentionality Of Mind Wanderingmentioning
confidence: 99%